ELKS, a Protein Structurally Related to the Active Zone-associated Protein CAST, Is Expressed in Pancreatic β Cells and Functions in Insulin Exocytosis: Interaction of ELKS with Exocytotic Machinery Analyzed by Total Internal Reflection Fluorescence Microscopy - Ohara-Imaizumi, Mica (The American Society for Cell Biology, 2005)
The cytomatrix at the active zone (CAZ) has been implicated in defining the site of Ca(2+)-dependent exocytosis of neurotransmitters. Here, we demonstrate the expression and function of ELKS, a protein structurally related to the CAZ protein CAST, in insulin exocytosis. The results of confocal and immunoelectron microscopic analysis showed that ELKS is present in pancreatic β cells and is localized close to insulin granules docked on the plasma membrane-facing blood vessels. Total internal reflection fluorescence microscopy imaging in insulin-producing clonal cells revealed that the ELKS clusters are less dense and unevenly distributed than syntaxin 1 clusters, which are enriched in the plasma membrane. Most of the ELKS clusters were on the docking sites of insulin granules that were colocalized with syntaxin 1 clusters. Total internal reflection fluorescence images of single-granule motion showed that the fusion events of insulin granules mostly occurred on the ELKS cluster, where repeated fusion was sometimes observed. When the Bassoon-binding region of ELKS was introduced into the cells, the docking and fusion of insulin granules were markedly reduced. Moreover, attenuation of ELKS expression by small interfering RNA reduced the glucose-evoked insulin release. These data suggest that the CAZ-related protein ELKS functions in insulin exocytosis from pancreatic β cells.